Extending the peer support specialist pathway for supporting recovery - Anthony Coetzer-Liversage; Pete Nelson; Ben Suker (Journal of Community Safety and Well-Being)
Recovery Corps is a pioneering social innovation in behavioural health, addressing the critical need for peer-driven recovery support services amidst the ongoing substance use crisis in the United States. Leveraging AmeriCorps infrastructure, Recovery Corps recruits and trains individuals with substance use disorder (SUD) lived experience to provide peer support in underserved communities. This narrative examines central assumptions associated with the Recovery Corps initiative, including those related to a perceived unmet demand for peer support, the feasibility of training community members without professional backgrounds, the impact of Recovery Corps peer support on recovery outcomes, and the degree to  which Recovery Corps experience creates career pathways for individuals in recovery. By bridging service gaps, enhancing recovery capital, and fostering sustainable workforce development, Recovery Corps offers a comprehensive model for integrating peer support within behavioural health frameworks. Lessons drawn from Recovery Corps underscore the importance of capacity building, flexible evaluation methods, and strategic partnerships to sustain and scale peer-driven interventions. This program highlights an adaptable approach to recovery support, presenting a model that may inform future social innovation in behavioural health.